A qualitative study on diverse experiences of medication safety among foreign-born persons living in Sweden - Lisa Hultin; Ulrika Pöder; Mariann Hedström; Anna Ekman; Katarina Hjelm (BMC, 2024)
Abstract Background The ongoing global migration has led to multicultural societies, with many migrants who do not speak the official language in the host country. This could contribute to communication problems with staff in healthcare and a risk to patient safety. Research on patient safety in medication use in migrants is an under-researched area. The aim was to explore diverse foreign-born people's experiences and perceptions of self-management of medication and determine if home-based practice patterns have implications on medication safety, and what factors may support safe medication use. Methods A qualitative explorative study, with individual semi-structured interviews and participant observations in the patients' home. Qualitative content analysis was applied. Results A purposeful sample of 15 foreign-born persons identified by healthcare staff as having language difficulties in Swedish that may pose a safety risk in connection with medication use at home, was selected. Three categories were identified. The first category showed respondents being dependent on another person, having experiences of not receiving information about their medications due to language barriers, having difficulties getting access to the healthcare centre and feeling distrusted/misunderstood. The second category showed respondents being independent and self-motivated Although they struggled, they managed to get access/contact with the healthcare centre themselves and felt understood/listened to by the staff. The last category concerned factors that facilitating medication use; such as having a medication list in the respondents' own language and offering a choice of language on the answering machine at the healthcare centre. Although they knew it was impossible to get an interpreter at the pharmacy, they felt safe knowing there was always a solution for receiving understandable information. Conclusion The findings highlighted that language barriers can complicate the communication between migrants and the healthcare, which can affect the medication safety. Understanding of this group is essential to improve the cooperation between patients and staff, leading to culturally congruent care. This knowledge should be used in healthcare to understand the gap in communication to increase patient safety. Further research from other angles, e.g. pharmacy/healthcare staff and relatives is needed to identify and evaluate facilitation to improve the outcome of the intended medication treatment.